INTRACRANIAL EXTRA-SKELETAL MESENCHYMAL CHONDROSARCOMA - Reyaz, Nadeem; Ashraf, Muhammad (Journal of Ayub Medical College Abbottabad, 2006)
Intracranial Mesenchymal Chondrosarcoma is a very rare and uncommon entity that affects young adults. We came across one such patient who presented with severe headache and intermittent nausea and vomiting. The clinical, radiological preoperative diagnosis was a meningioma, on histological examination it turned out to be mesenchymal chondrosarcoma of tentorial region in posterior fossa, uncommon site for this entity. Keywords: Mesenchymal chondrosarcoma, Tentorium, Meningioma